2013
DOI: 10.1158/1055-9965.epi-12-0987
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors Predict Higher Interleukin-6 Levels among Patients Newly Diagnosed with Head and Neck Squamous Cell Carcinoma

Abstract: Background Health behaviors have been shown to be associated with recurrence risk and survival rates in cancer patients and are also associated with Interleukin-6 levels, but few epidemiologic studies have investigated the relationship of health behaviors and Interleukin-6 among cancer populations. The purpose of the study is to look at the relationship between five health behaviors: smoking, alcohol problems, body mass index (a marker of nutritional status), physical activity, and sleep and pretreatment Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 70 publications
(78 reference statements)
2
39
0
Order By: Relevance
“…Recently, Duffy and colleagues found that smoking was independently associated with a higher serum interleukin-6 (IL-6) level among patients with head and neck cancer (27), and a higher IL-6 level was predictive of an increased risk of recurrence and poorer OS (28). In nasopharyngeal carcinoma, IL-6 facilitates tumor carcinogenesis and malignancy enhancement via activation of the STAT3, and a higher IL-6 level is associated with advanced stage nasopharyngeal carcinoma (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Duffy and colleagues found that smoking was independently associated with a higher serum interleukin-6 (IL-6) level among patients with head and neck cancer (27), and a higher IL-6 level was predictive of an increased risk of recurrence and poorer OS (28). In nasopharyngeal carcinoma, IL-6 facilitates tumor carcinogenesis and malignancy enhancement via activation of the STAT3, and a higher IL-6 level is associated with advanced stage nasopharyngeal carcinoma (29).…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell head and neck carcinomas are highly inflammatory in nature and express a number of cytokines and growth factors involved in inflammation (47). Specifically, pretreatment serum IL6 levels have been found to predict recurrence and poor survival in head and neck cancer (48); smoking is associated with high IL6 levels, and this may result from the adverse effects of smoking on sleep patterns (49). Beyond this, the consequences of smoking-induced inflammation and immune dysregulation are not well understood (50).…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…26,27,31,32,36,[54][55][56][57][58][59][60] Elevated concentrations of IL-6 were found in the saliva of patients with premalignant HNSCC lesions. 26 Higher pretreatment serum IL-6 levels were associated with lower HNSCC overall survival, higher tumor recurrence, and increased development of second primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…26 Higher pretreatment serum IL-6 levels were associated with lower HNSCC overall survival, higher tumor recurrence, and increased development of second primary tumors. 26,31,36,59 In patient HNSCC tumor tissue specimens, IL-6 levels correlated with the HNSCC tumor grade and were reduced after effective radio-or chemotherapies. 55,57 IL-6Ra mRNA levels were higher in oral cancer cells relative to normal mucosa, and increased IL-6Ra expression was associated with larger tumors of advanced histological stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation